Religious behavior in early childhood: internalization of values and habituation in the school environment - Abid Al Faqh, Muhammad; Sirait, Sangkot (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2026)
Background: Religious behavior in early childhood is frequently observed within structured educational settings. However, children who appear religious at school do not always demonstrate the same level of awareness and practice outside the school environment. This phenomenon raises questions about whether such behaviors reflect genuine value internalization or are primarily the result of habituation. Objective: This study aims to examine whether early childhood religious behaviors represent the internalization of Islamic values or are predominantly shaped by repeated habituation practices in the school environment. Methods: A qualitative descriptive approach was employed involving five children aged 5–6 years and five parents at PAUD Pijar Beriman, Dasan Agung Baru. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model developed by Matthew B. Miles and A. Michael Huberman. Result: The findings indicate that children are able to perform various religious practices, including prayer, ablution, Qur’an recitation, and daily supplications within the school setting. Nevertheless, these behaviors are not consistently initiated independently at home and continue to depend on parental encouragement. Based on Muhaimin’s framework of value internalization, the children have reached the stages of value recognition and practice but have not yet attained the stage where religious values become an integral part of their inner awareness. Conclusion: The study concludes that religious behavior among the participating children is more strongly influenced by habituation than by deep value internalization. Although religious practices have become part of their daily routines at school, the process of transforming these practices into intrinsic personal values remains incomplete.